Mastery Learning Based Elementary School Learning for Philippines’ Students with the Schneeball-Wirbelgruppe Model - Marie Freddie Gladys; Isaiah Jacinto Naparan (Program Studi PGSD Universitas Madako Tolitoli, 2025)
21st century learning demands mastery of scientific thinking concepts and skills through collaborative approaches and active discussion. This study aims to analyze the effectiveness of the Schneeball-Wirbelgruppe learning model in improving the mastery of concepts in the science material studied by students. The study took place in Lam-an, Ozamiz City, Misamis Occidental, Philippines, focusing on an elementary school namely Philippine Schools Overseas (PSO). The study uses a one-group pretest-posttest class experimental design with a sample of 19 elementary school students in 2025. The instrument used is a concept mastery test in the form of multiple choice and descriptions that have been validated and reliable. Data were analyzed using descriptive (N-gain test) and inferential (paired t-test) analysis. The results showed a significant increase between pretest and posttest scores, indicating that the Schneeball-Wirbelgruppe model was effective in improving conceptual mastery, especially in science learning. These findings suggest that the model can be an alternative to innovative learning strategies that support students' conceptual understanding in a more in-depth way. The implication of this study is that the Schneeball-Wirbelgruppe model has the potential to be applied to a wide range of other concepts and subjects at the elementary school level.